Analisis Kesulitan Belajar Matematika Materi Perkalian Pada Siswa Kelas III Sekolah Dasar - Dian Aprilia Kusumasari; Drs. Kiswoyo, M.M; Ryky Mandar Sary, S.Pd., M.Pd (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2021)
The difficulty of learning multiplication counting operations is a difficulty that is still experienced by many students. It is interesting to do further research. This study aims to identify the difficulties in learning multiplication experienced by grade 3 students at SD Negeri Pandeanlamper 04 Semarang and identify the causal factors. The research method used is descriptive qualitative research method. The subjects of this study were teachers and third grade students of SD Negeri Pandeanlamper 04 Semarang. The results of the analysis show that (1) difficulties in learning multiplication counting operations include difficulties in calculation skills, difficulties in using the wrong process, difficulties in determining place values, difficulties in unreadable writing, and difficulties in understanding symbols, 2) factors that cause difficulties in learning multiplication include attitudes in learning, student interest in learning, student motivation in learning, student habits when studying, parental attention to student learning activities, teacher-student relationships, student and teacher discipline, media and tools available learning support, as well as school and classroom conditions. This shows that the difficulties in learning multiplication experienced by students are caused by internal factors and external factors.